PUSAT KULINER SEAFOOD DI MUARA LAUT SUNGAI KAKAP, KABUPATEN KUBU RAYA - Tri Rivaldi; Syaiful Muazir; Affrilyno Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
Indonesia is a maritime country because it has an area of water reaching 3.25 million km2 or about 63%. The sea mouth of the Sungai Kakap, Kubu Raya regency, is part of the Indonesian maritime region that has fisheries management or WPP711 Natuna Sea, making it the second largest fish producing region in West Kalimantan. Sungai Kakap is part of a strategic tourism area that can be further developed. UnfortuUnfortunately, it wasn’t felt the benefits by the surrounding community. Based on these, the architectural response must offer a place containing the results of the marine resources of culinary-tourism based on Sungai Kakap and connected to the existing restaurant as the Seafood Culinary Center of Sungai Kakap Estuary. By realizing a cooperative system with the Sungai Kakap community, it is hoped that the design will improve the quality of life of the residents of Sungai Kakap. Applying the glass box method, planning becomes more objective, using the information obtained during data collection, which is supported by a clear conceptual analysis and synthesis. With a land area of 1.39 hectares, Sungai Kakap Estuary Seafood Culinary Center consists of a new mass area, an existing masses area and a space connecting the masses. The new area masses will consist of a restaurant function with different services than the current restaurant/market place, and a workshop/community-kitchen with movable internal walls. A connecting space used as a plaza and for culinary events.